Economic rights and justice: of walls and bridges, exclusions and inclusions (2018)
The paper discusses socio-economic rights and the extent to which it offers protection for the dignity, freedom and well being of citizens in their states. The paper further considers the raging debate on whether to include or exclude the application of these rights into national constitutions with a view to serving the essence of justice. The paper highlights legal implications of clear cut separation and the imperatives of fusion of the basic components of socio-economic entitlements to education, health care, housing living wage, decent working conditions and social infrastructure for human development